[PP.18.14] ASSOCIATION BETWEEN ONE-HOUR POST-LOAD PLASMA GLUCOSE LEVELS AND ARTERIAL STIFFNESS IN NORMOTENSIVE SUBJECTS WITH NORMAL GLUCOSE TOLERANCE. (September 2017) - Nakagomi, A.; Sunami, Y.; Okada, S.; Ohno, Y.; Shoji, T.; Fujisawa, T.; Kobayashi, Y.
Abstract : Objective: Elevated one-hour post-load plasma glucose (1h-PG) during an oral glucose tolerance test is associated with subclinical organ damage like carotid atherosclerosis and left ventricular hypertrophy. The aim of this study was to investigate whether 1h-PG affects arterial stiffness, determined by brachial-ankle pulse wave velocity (baPWV), in normotensive subjects with normal glucose tolerance (NGT). Design and method: Study subjects were 25-, 30-, 35-, 40-, 45-, 50- and 55-year-old non-industrial workers (n = 8381) who underwent a regular health check-up programme every 5 years. We included only subjects with NGT according to the American Diabetes Association criteria, namely, fasting plasma glucose concentrations of < 100 mg/dL and 2-hour post glucose load plasma glucose (2h-PG) concentrations of <140 mmHg and HbA1c level < 5.7%. We excluded subjects with hypertension, taking any medication, and having an abnormal ankle–brachial index (ABI) (ABI < = 1.0, ABI >=1.3). The final sample consisted of 4970 participants (2048 female). Results: 1h-PG showed significant correlation with baPWV only in male subjects, but not in female subjects (male: r = 0.18, p < 0.001, female: r = 0.02, p = 0.30). The correlation in male subjects remained significant after adjustment for confounders (male: β = 0.04, p = 0.02, female: β = −0.03, p = 0.10). Fasting plasma glucose (FPG) and 2-hour plasma glucose (2h-PG) did not significantly correlate with baPWV in multivariate analysis in male subjects (FPG: β = 0.018, p = 0.25; 2h-PG: β = −0.002, p = 0.89). As we found significant interaction between 1h-PG and age (p = 0.04) in male group, we performed analysis in each age-subgroup. After adjustment for possible confounders, the correlations between 1h-PG and baPWV was significant in 55-years-of-age group (β = 0.11, p = 0.02) and border significant in 45-years-of-age group (β = 0.07, p = 0.09) and 50-years-of-age group (b = 0.08, p = 0.08). In these groups, baPWV values of subjects had 1h-PG > = 155 mg/dl were significantly higher than those of subjects had 1h-PG <155 mg/dl. Conclusions: Elevated 1h-PG was associated with arterial stiffness in middle-aged male subjects with normotension and NGT.